National Interest of the Republic of Serbia for Participation of Serbian Armed Forces in Peacekeeping Operations - Radojević, Slobodan (Serbian political thought, 2024)
Peacekeeping operations are one of the instruments for resolving crises in the world and preventing armed conflicts that threaten global peace and security. This article argues that the participation of the Serbian Armed Forces in UN missions contributed to the peacekeeping in the world and produced positive benefits for the country. Namely, Serbian Armed Forces inherits the tradition of many years of participation in UN and EU peacekeeping operations. This article first reviews the most relevant milestones of Republic of Serbia’s contribution to peacekeeping operations, focusing on the important role played by defence and foreign policies in national development and international cooperation. This is followed by a presentation of national legislation governing the participation of military personnel in peacekeeping operations. Therefore, peacekeeping operations are recognized as a type of multilateral mechanism for achieving cooperation between the Republic of Serbia and UN/EU and a contribution to building trust and the position of a reliable partner in international relations. The theory of international relations that explains such actions of states is the realism theory. In accordance with realists school of thought, state national interests for participation in peacekeeping operations are military security issues, national and strategic interests as well as economic interests, and increased credibility and power of stаtes in international relations. Starting from the fact that global security is comprehensive and indivisible, states are even more interested in participating in peacekeeping operations and perceive it as their national interests and an element of foreign and security policy. This is the initial thesis from which the authors base their analysis presented in the paper.